IMPLEMENTASI TRANSFORMASI DIGITAL DALAM MEMBANGUN BUDAYA LITERASI DIGITAL GURU DI SMP PGRI KECAMATAN PONDOK LABU JAKARTA SELATAN - Indayani Indayani; Imas Masriah; Sri Utaminingsih (Jurnal Manajemen Pendidikan, 2025)
Digital transformation in the educational context requires teachers to possess adequate digital literacy competencies to integrate technology into learning. This study aims to describe the implementation of digital transformation in building a digital literacy culture among teachers at SMP PGRI, Pondok Labu District, South Jakarta. The research approach used a qualitative descriptive method with data collection techniques through observation, in-depth interviews, and documentation. The results indicate that the digital transformation process has been ongoing but is not yet optimal. Teachers still experience obstacles in the use of digital devices, utilization of learning platforms, and consistency in implementing digital literacy practices. The main inhibiting factors include limited training, unstable network infrastructure, and low teacher confidence in using technology. Nevertheless, the school is committed to providing technological facilities and encouraging a shift in work culture towards a digital-based learning environment. This study emphasizes the importance of continuous training, technological assistance, and the provision of adequate infrastructure to accelerate teachers' digital literacy culture comprehensively.